Optimization of load frequency control permancein two-area power system with PID controller using ICA and GSA algorithms / Mumuney Nurullahi Lekan - Mumuney Nurullahi , Lekan (2018)
The importance of load frequency control (LFC) in the field of power system cannot be denied due to the necessity in the demand of a reliable and stable power supply. LFC in power systems is used to stabilize and regulate the electrical power supply in a nested area power system. The change in the system is signified by the change in the system frequency and tie-line (T-L) load. The performance of LFC has to be tuned properly so that the response can be optimized with a selected controller and algorithm for optimization. Hence, in this project, imperialist competitive algorithm (ICA) and gravitational search algorithm (GSA) are proposed in a LFC of two-area power system to optimize the performance of PID controllers using MATLAB and Simulink. The PID controller is used as a control unit to improve the performance of the LFC in the presence of perturbation in the system. A comparative study performed based on the proposed algorithms clearly shows that the performance of GSA-PID is superior over ICA-PID controller in terms of the rise time and the settling time during perturbation or disturbance in the system. Keywords: Load Frequency Control (LFC), Gravitational Search Algorithm (GSA), Imperialistic Competitive Algorithm (ICA), Tie-Line (T-L).